Pre-treatment of mscanthus sinensis with Bacta-sile to aid anaerobic digestion - Jegede, Abiodun O. (International Journal of Agricultural and Biological Engineering, 2013)
The investigation of the biodegradability and methane potential of bacterial pre-treated miscanthus sinensis has been carried out. One percent solution of Bacta-sile: A silage promoter was used to pre-treat miscanthus sinensis at 25